Preoperative applications of cortical mapping with functional magnetic resonance. - Cravo, I (2001)
The authors describe a clinical experience in cortical brain mapping by Functional Magnetic Resonance Imaging (FMRI) with a 1.0 T MR scanner with BOLD technique and echo-planar imaging (EPI). A brief review is made of the theoretical basis of the BOLD technique and of the different functional tasks used. The main clinical applications of FMRI cortical mapping regarding the sensorimotor cortex of the hand and of language are mentioned. The experiment involves 29 patients, 16 with gliomas (G), 7 with mesial temporal sclerosis (MT S) and 6 with arteriovenous malformations (AVM) The most frequent clinical applications were the determination of the topographic relationship of the cerebral lesions with these eloquent cortices as well as the presurgical lateralization of language in medically intractable epileptic patients. The results are discussed in order to assess the FMRI cortical mapping role as a noninvasive method for presurgical planning, regarding the evaluation of the potential neurosurgical risks and the identification of viable cortex regions displaced or reorganized as a consequence of disease. Additionally, FMRI cortical mapping can also assess the atypical speech representations and the language lateralization of the patients.